Analisis Strategi Pemasaran Event Marketing dan Cross Selling terhadap Peningkatan Penjualan & Keputusan Pembelian Produk “Keke Busana” di Lamongan - Riska Anik Dwi Apriliana; Indira Shofia Maulida; Moh. Muklis Sulaeman; Dhita Dhora Damayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to find out and analyze the Marketing Strategy of Event Marketing and Cross Selling on the Increase in Sales and Purchase Decisions on the product Keke Busana in Lamongan. The type of research used is quantitative descriptive. The population in this study is all visitors and customers who make purchases at the Keke Jetis Lamongan Terrace. The sampling method used in this study was random sampling of 86 respondents. The data analysis methods used in this study are validity test, reliability test, classical assumption test, multiple linear regression analysis, determination coefficient test, t test and f test with the help of SPSS version 29. The results of this study show that there is a partially significant positive influence between the variables of Event Marketing, Cross Selling on Sales Increase and Purchase Decisions of Keke Clothing products in Lamongan with the t value calculated > t table (t calculate X1 against Y1 = 2,647, X2 against Y1 = 5,800, while t calculate X1 against Y2 = 3,716 and X2 against Y2 = 4,917). Simultaneously, there was a significant positive influence between the variables of event marketing and cross selling on Y1 with an F value of 54,970 > Ftable 4.87, and on Y2 = 56,066 >Ftable 4.87.In this study, the Cross Selling variable has the most dominant influence on the Increase in Sales and Purchase Decisions of Keke Busana products in Lamongan.